PENGARUH LATIHAN PLYOMETRICS TERHADAP PENINGKATAN KEMAMPUAN THREE POINT SHOOT - Muhammad Ghibran Jalil; Adnan Fardi; John Arwandi; Ronni Yenes (Universitas Negeri Padang, 2020)
The problem in this study is the lack ofability of three point shoot the male athlete Dharma Muda Dharmasraya. The variables in this study wereexercise plyometrics and the ability of the three point shoot. The purpose of this study was to determine the effect oftraining plyometrics on the improvement of theability of three point shoot male athletes Dharma Muda Dharmasraya. This type of research is a pre-experiment which aims to see the effect oftraining plyometrics on improving the ability of three point shoots. The population in this study were all male basketball athletes, Dharma Muda Dharmasraya, totaling 17 people. Sampling was done by purposive sampling technique, namely male athletes Dharma Muda Dharmasraya as many as 10 people. To obtain research data, theability test was used three point shoot. The data obtained were analyzed by using the t test. Based on the results of data analysis, it is known thattraining plyometrics has a significant effect on the improvement of theability three point shoot. Where theaverage of pre-test theability three point shoot was 16.1 while the post test increased to 22.8. Then obtained the mean difference test (t test) of tcount 10.30 while ttable 2.26 with a significant level α = 0.05 and n = 10, then tcount > ttable (10.30> 2.26), it can be concluded that there is a significant effect of the form oftraining plyometrics on the improvement of theability of three point shoot the male athlete Dharma Muda Dharmasraya.